Research Progress on the Dendrolimus spp. Pheromone: From Identification to Molecular Recognition - Zhang, Sufang; Kong, Xiangbo; Zhang, Zhen (Frontiers in Cell and Developmental Biology, 2022)
Dendrolimus species (Lepidoptera, Lasiocampidae), are the most serious phytophagous pests of coniferous forests worldwide. Dendrolimus feed intensively on needles, leading to considerable economic loss and ecological damage. Notably, the outbreak of Dendrolimus is a somewhat periodic pattern, those outbreaks causing rapid and large-scale destruction of pine forests, with those forests observed to look like “Fire without smoke.” Sex pheromones play an important role during insect mating and reproduction, and there has been extensive research into the pheromone of Dendrolimus. The pheromone components of several Dendrolimus have been identified, and functions of two most important pheromone recognition genes, pheromone binding proteins (PBPs) and pheromone receptors (PRs) were clarified. The evolution of PBP gene sequences is in good agreement with the trends in structural changes of the sex pheromone components in several Dendrolimus species, and it is interesting that PRs of Dendrolimus spp. occupy a novel lineage of PRs tuned to Type I pheromones in Lepidoptera. We present the current state of research into the sex pheromone of these important forest pests and highlight the emerging topics, to clarify future urgent work into Dendrolimus.